Understanding the sharing economy and its implication on sustainability in smart cities - Akande, Adeoluwa (2020)
Akande, A., Cabral, P., & Casteleyn, S. (2020). Understanding the sharing economy and its implication on sustainability in smart cities. Journal of Cleaner Production, 277, 1-11. [124077]. https://doi.org/10.1016/j.jclepro.2020.124077